Penerapan Kunyit Sebagai Indikator Asam-Basa dalam Pembelajaran Sains di Madrasah Ibtidaiyah Ihya Ulumiddin Banjarmasin: Perspektif Siswa - Gusti Hadiatus Solehah (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This study aims to explore the application of turmeric as an acid-base indicator in science learning at Madrasah ibtidaiyah ihya ulumiddin banjarmasin, as well as to understand students' perspectives on the use of turmeric in acid-base reaction experiments. The research method employed is a qualitative approach, utilizing interviews and observations with students at the madrasah. In the experiment, turmeric is used to indicate pH changes in solutions of Sunlight soap as a base and lime juice as an acid. The findings reveal that students have a good understanding of the acid-base concept and recognize the benefits of using turmeric as a natural, easily accessible, and environmentally friendly indicator. Based on interview results, students also expressed that this experiment made science learning more engaging and easier to comprehend. This study is expected to provide new insights into more contextual and applicable science teaching at the madrasah level.